Historical links between Latin American psychology and pedagogy in experimentation - Arias, Walter L. (2014)
This work sets out historical information about the development of Latin American psychology over the base of education. It reviews the contribution from education to Latin American psychology, and especially, the creation of experimental psychology laboratories in schools and educational and psychopedagogical institutions, where experimental pedagogy laboratories operate, which were a relevant antecedent for psychology’s institutionalization through the creation of Programs and Professional Schools.